Physical activities patterns among Indonesian pregnant women: a cross-sectional study - Elliza Widi Lestari; Sharon Gondodiputro; Neneng Martini; Indria Yulita (Intelektual Pustaka Media Utama, 2023)
Many evidence revealed that physical activity (PA) has positive effects on pregnancy outcomes. Healthy pregnant women are suggested to have a combination of PA in light to moderate-intensity activities for 150 minutes per week. The purpose of this study was to analyze the type, the intensity of PA of pregnant women, and the average energy expenditure per week. A cross-sectional study involving 110 pregnant women who came from four community health centers in Bandung city, Indonesia was carried out from April to June 2021. The pregnancy physical activity questionnaire (PPAQ) was used to collect data. Descriptive data were presented using median and percentile. Mann-Whitney and Kruskal Wallis test were used to statistical test. The results of the study where the median energy expenditure per week was 250.50 METs. Most of the PA was light-intensity activities and household/child caring activities. There were still 10% pregnant women who did not exercise. Employed pregnant women had energy expenditure per week higher compared to unemployed pregnant women. Sports/exercise activities were seldom been carried out. This study demonstrated that during pandemic COVID-19, pregnant women are still doing PA. During pandemic COVID-19, health care providers should motivate healthy pregnant women to exercise by creating innovations using social media or online platforms so that pregnant women can exercise at home safely.